Whole genome sequencing of ovarian granulosa cell tumours show heterogeneity, genomic instability and tumour evolution. (1st November 2019) - Roze, JF; Monroe, GM; Groeneweg, JW; Stelloo, E; Paijens, ST; Nijman, HW; van Meurs, HS; Lonkhuijzen, LRCW van; Piek, JMJ; Lok, CAR; Jonges, GN; Zweemer, RP
Abstract : Introduction/Background: Adult granulosa cell tumours (aGCTs) are thought to arise from the stromal cells of the ovary and are molecularly characterized by a specific FOXL2 c.402C>G mutation. Cytoreductive surgery remains the mainstay of treatment of both primary and recurrent disease, because the effect of chemotherapy is limited. Unravelling this tumour on a genomic level could possibly identify targets for systemic therapy. However, most genomic studies on ovarian cancer do not focus on aGCTs. We investigated the genomic landscape and tumour stability of aGCTs, a crucial step towards targeted treatment. Methodology: We performed whole genome sequencing (WGS; 30–90X coverage) on 31 fresh frozen aGCT samples (5 primary aGCTs and 26 recurrences) to detect single nucleotide variants and copy number variants. From 23 samples matched germline DNA was available, enabling somatic variation identification. We compared multiple tumour samples taken from the same patient at different locations and time points. The cohort will be further extended to identify novel (targetable) cohort mutations and affected pathways. Results: Cohort analysis detected the FOXL2 mutation in 90% (28/31 samples) and a TERT promoter mutation in 68% ( C228T in 14/31 and C250T in 7/31) of samples. Copy number analyses showed polyploidy in 70% of the matched samples (16/23) and confirmed previous reported gains in chromosome 14 and losses in 22. Intra-patient comparisons showed 40–72% unique somatic variants with 1562–1650 overlapping somatic variants detected in all samples. Somatic variant analysis in the matched samples showed 1431 to 8102 (median 4103) single nucleotide variants and 462 to 2963 (median 2065) insertions/deletions. Conclusion: The view of aGCTs as monogenetic and genetically stable is no longer supported. The large number of unique somatic mutations in intra-patient comparisons reveals a high degree of tumour heterogeneity. Future targeted treatment should focus on consistent genomic changes shared both between and within patients. Disclosure: No competing interests. Applicable funding sources: Granulosafonds Philine van Esch.